2023
DOI: 10.3390/ani13132171
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Consequences of Oxygen Imbalance on Early Embryo Development: Exploring Mitigation Strategies

Abstract: Although well-established and adopted by commercial laboratories, the in vitro embryo production system still requires refinements to achieve its highest efficiency. Early embryonic development is a dynamic event, demanding suitable conditions to provide a high number of embryos with quality and competence. The first step to obtaining an optimized in vitro environment is to know the embryonic metabolism and energy request throughout the different stages of development. Oxygen plays a crucial role in several ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Normal embryo development relies on proper cellular homeostasis, but oxidative stress significantly impacts this process. Various factors may contribute to cellular and oxidative stress during embryo culture including oxygen tension 50 , glucose concentration 12 , light, temperature, culture media supplements and culture equipment 51 . Increased stress levels during embryo culture can lead to detrimental effects such as increased genomic instability 52 and endoplasmic reticulum (ER) stress 12 , 52 , which can activate the unfolded protein response (UPR) and trigger cell death 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal embryo development relies on proper cellular homeostasis, but oxidative stress significantly impacts this process. Various factors may contribute to cellular and oxidative stress during embryo culture including oxygen tension 50 , glucose concentration 12 , light, temperature, culture media supplements and culture equipment 51 . Increased stress levels during embryo culture can lead to detrimental effects such as increased genomic instability 52 and endoplasmic reticulum (ER) stress 12 , 52 , which can activate the unfolded protein response (UPR) and trigger cell death 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we observed that supplementation of the culture medium with the antioxidant melatonin was unable to rescue development of NRF2-attenuated embryos cultured in excess glucose. It is well established that antioxidant supplementation improves porcine embryo development 22 , 50 . Melatonin was chosen as the antioxidant for this study due to its known effects in ameliorating oocyte maturation and embryo development 18 , 21 , 27 , 30 , mitigating the detrimental consequences of excess glucose on embryo development, improving glucose metabolism in adult mice by upregulating hepatic FBXL7 expression 20 , and its proposed role in alleviating oxidative stress through NRF2 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that low oxygen tension plays a key role in reducing high levels of harmful reactive oxygen species (ROS) in cells, influencing embryo gene expression, helping embryo glucose metabolism, and accelerating embryo development to the blastocyst stage [73]. It has been suggested that culture under reduced oxygen tension is critical for maintaining physiological embryo development and increasing reproductive competence.…”
Section: Oxidative Stressmentioning
confidence: 99%

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Biomolecules
“…Although seminal plasma contains enzymatic and non-enzymatic antioxidants, they become present in trace amounts after washing and dilution with cryo-media, resulting in an imbalance between ROS and natural scavenger activity after freezing. This imbalance decreases the cleavage rate, embryo development, and blastocyst formation after fertilization [ 16 ]. Despite ongoing efforts to mitigate these issues through the application of exogenous antioxidants, artificial insemination (AI) requires large semen volumes and typically results in lower conception rates than natural fertilization using fresh semen.…”
Section: Introductionmentioning
confidence: 99%